2007
DOI: 10.1111/j.1467-8624.2007.01098.x
|View full text |Cite
|
Sign up to set email alerts
|

How Toddlers and Preschoolers Learn to Uniquely Identify Referents for Others: A Training Study

Abstract: This training study investigates how children learn to refer to things unambiguously. Two hundred twenty-four children aged 2.6, 3.6, and 4.6 years were pre- and posttested for their ability to request stickers from a dense array. Between test sessions, children were assigned to a training condition in which they (a) asked for stickers from an adult, (b) responded to an adult's requests for stickers, (c) observed 1 adult ask another for stickers, or (d) heard model descriptions of stickers. All conditions yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
1
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(130 citation statements)
references
References 45 publications
4
118
1
7
Order By: Relevance
“…Children typically develop adult-like abilities to spontaneously produce unambiguous referring expressions in simple contexts by approximately six years of age (Dickson, 1982;Girbau, 2001;Matthews, Lieven, & Tomasello, 2007). It has been suggested that their production of under-informative referring expressions prior to this age is due to a lack of awareness of other potential targets in the environment (Whitehurst, 1976) or because they don't realise that to refer means to implicitly describe differences that will eliminate potential ambiguity (Whitehurst & Sonnenschein, 1981).…”
Section: Typical and Atypical Development Of Referencementioning
confidence: 99%
“…Children typically develop adult-like abilities to spontaneously produce unambiguous referring expressions in simple contexts by approximately six years of age (Dickson, 1982;Girbau, 2001;Matthews, Lieven, & Tomasello, 2007). It has been suggested that their production of under-informative referring expressions prior to this age is due to a lack of awareness of other potential targets in the environment (Whitehurst, 1976) or because they don't realise that to refer means to implicitly describe differences that will eliminate potential ambiguity (Whitehurst & Sonnenschein, 1981).…”
Section: Typical and Atypical Development Of Referencementioning
confidence: 99%
“…An example hierarchy that summarises what might be learnt is that put forward by Gundel and colleagues (Gundel et al 1993;Gundel et al 2001). That children need to learn such properties of referring expressions is assumed to be uncontroversial, even if how this is achieved is currently a matter of debate (Matthews et al 2006;Matthews et al 2007). …”
Section: A Cognitive Grammar Account Of Anaphora (Van Hoek 1997)mentioning
confidence: 99%
“…Beyond the scope of this chapter is the large literature on the development of reference which lends useful insights from children's use of overspecified reference to the current debate (e.g., Flavell et al 1981;Dickson 1982;Sonnenschein & Whitehurst 1984;Revelle et al 1985;Lloyd, Mann & Peers 1998;Matthews et al 2006Matthews et al , 2007Huang & Snedeker 2008;Davies & Katsos 2010;Nilsen & Graham 2012;Bannard, Klinger & Tomasello 2013;Morisseau, Davies & Matthews 2013). We expect that future endeavours will continue in tandem with these areas.…”
Section:  Future Directionsmentioning
confidence: 99%